Persepsi Pekerja Terhadap Tingkat Kesejahteraan Di Pengumpul Rotan UD Putra Harapan: Workers' Perceptions of Welfare Levels At the UD Putra Harapan Rattan Collector - Purba, Brima Juntama; Jemi, Renhart; Koroh, Desy Natalia; Nursiah, Nursiah; Nuwa, Nuwa (HUTAN TROPIKA, 2024)
Rattan is a type of palm tree that grows in tropical climates. Rattan currently has a low price level with limited rattan raw materials. However, rattan collectors continue to buy rattan from farmers and provide jobs for their workers with low wages, but rattan workers continue to work. Based on this background, research was conducted which aimed to analyze the level of worker welfare based on the Regional Minimum Wage (UMR) and the Central Statistics Agency (BPS); as well as knowing workers' perceptions of their level of welfare at UD Putra Harapan. The data collection method uses observation and structured interviews with key respondents. Data analysis uses a Likert Scale to measure respondents' perceptions and uses analysis of worker welfare levels based on UMR and BPS. The research results show: the level of welfare of workers does not meet the minimum wage individually, but if we look at each household, the respondent's income exceeds the minimum wage. Meanwhile, based on BPS, the level of worker welfare is included in the high classification. The perception of rattan workers at UD Putra Harapan states that their level of welfare is relatively good.